2019
DOI: 10.1177/2378023118823946
|View full text |Cite
|
Sign up to set email alerts
|

Who Counts as a Notable Sociologist on Wikipedia? Gender, Race, and the “Professor Test”

Abstract: This paper documents and estimates the extent of underrepresentation of women and people of color on the pages of Wikipedia devoted to contemporary American sociologists. In contrast to the demographic diversity of the discipline, sociologists represented on Wikipedia are largely white men. The gender and racial/ethnic gaps in likelihood of representation have exhibited little change over time. Using novel data, we estimate the "risk" of having a Wikipedia page for a sample of contemporary sociologists. We sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 34 publications
0
44
0
3
Order By: Relevance
“…3 Some recent projects have also begun to unpack the "gap" by looking at the ways in which it emerges. 4 Although this follow-on work presented a range of different estimates of the scope of the gap in participation between male and female editors, none of the work overturned the basic conclusion that Wikipedia's editor base appears largely, if not overwhelmingly, made up of men.…”
Section: The Gender Gapmentioning
confidence: 90%
“…3 Some recent projects have also begun to unpack the "gap" by looking at the ways in which it emerges. 4 Although this follow-on work presented a range of different estimates of the scope of the gap in participation between male and female editors, none of the work overturned the basic conclusion that Wikipedia's editor base appears largely, if not overwhelmingly, made up of men.…”
Section: The Gender Gapmentioning
confidence: 90%
“…The gender distribution of biographies has also been compared with the gender distribution of actual social groups. For example, one study compared U.S. sociologists with their Wikipedia record and found that men are twice as likely as women to have a biographical article (Adams et al, 2019), which confirms the coverage asymmetry's relevance.…”
Section: Content Selectionmentioning
confidence: 95%
“…Editors maintain the possibility to propose the deletion of articles, which initiates an internal process of debate (called 'Article for Deletion' discussion) that can lead to four outcomes: the article is kept, deleted, merged with another, or redirected to another (Taraborelli & Ciampaglia, 2010). Studies that have tested gender trends in this process have found no systematic asymmetries: there are no more deletions of content about women or more nominations to remove content about women (Adams et al, 2019;Worku et al, 2020). This suggests that the main challenge for female representation is in the original selection process and not in this subsequent review stage.…”
Section: Content Selectionmentioning
confidence: 99%
“…Some inaccurate information has, of course, been added to Wikipedia, but most of these falsehoods are removed shortly after being published on the site (Halavais, 2004). The more legitimate, consequential biases on Wikipedia instead are those that reflect the limited and/or missing content and the narrow range of editors of the pages (called Wikipedians; Adams et al, 2019). The major culprit stems from systemic bias in Wikipedia.…”
Section: Introductionmentioning
confidence: 99%
“…The major culprit stems from systemic bias in Wikipedia. Wikipedia's content is reflective of a racial and gender bias in the significantly lower rates of participation on the site as editors by women and people of color (Adams et al, 2019;Lim & Kwon, 2004;Racial Bias, 2020). The typical Wikipedian is a white, educated male from a middle class background (Systemic Bias, 2020).…”
Section: Introductionmentioning
confidence: 99%